APORTE FLUVIAL E DISPERSÃO DE MATÉRIA PARTICULADA EM SUSPENSÃO NA ZONA COSTEIRA DO RIO SÃO FRANCISCO (SE/AL) - Medeiros, P. R. P.; Knoppers, B. A.; dos Santos Júnior, R. C.; Souza, W. F. L. (Geochimica Brasiliensis, 2012)